2007
DOI: 10.1177/1049731506296196
|View full text |Cite
|
Sign up to set email alerts
|

The Chinese Positive Youth Development Scale

Abstract: Objective: This article describes the development and initial validation of the 90-item Chinese Positive Youth Development Scale (CPYDS), which contains items related to 15 aspects of positive youth development. Method: Adolescents with well adjustment (N = 162) and poor adjustment (N = 160) responded to the CPYDS. Results: The findings showed that the CPYDS measures possess acceptable internal consistency and were able to discriminate the two groups. Although the CPYDS measures were positively related to thri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
150
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 224 publications
(168 citation statements)
references
References 33 publications
2
150
0
2
Order By: Relevance
“…Positive Youth Development The Chinese Positive Youth Development Scale (CPYDS; Shek et al 2007) was utilized to measure students' developmental outcomes. Previous research demonstrated that this scale had sound psychometric properties (Shek and Ma 2010Shek and Ma 2014a, b).…”
Section: Methodsmentioning
confidence: 99%
“…Positive Youth Development The Chinese Positive Youth Development Scale (CPYDS; Shek et al 2007) was utilized to measure students' developmental outcomes. Previous research demonstrated that this scale had sound psychometric properties (Shek and Ma 2010Shek and Ma 2014a, b).…”
Section: Methodsmentioning
confidence: 99%
“…The CPYDS was developed by Shek et al (2007), which had 15 subscales corresponding to 15 constructs of positive youth development attributes proposed by Catalano et al (2002). This instrument has shown sound validity and reliability in measuring Chinese young people's positive attributes in previous studies (Shek and Ma 2010).…”
Section: Dimension 1-effective Reasoning and Problem Solvingmentioning
confidence: 99%
“…The third indicator, cognitive-behavioral competence, concerned students' skills in solving problems by thinking independently and taking effective actions in Chinese Positive Youth Development Scale (CPYDS) (Shek and Ma 2010;Shek et al 2007). The CPYDS was developed by Shek et al (2007), which had 15 subscales corresponding to 15 constructs of positive youth development attributes proposed by Catalano et al (2002).…”
Section: Dimension 1-effective Reasoning and Problem Solvingmentioning
confidence: 99%
“…Positive Youth Development The Chinese Positive Youth Development Scale (CPYDS: Shek et al 2007 ) was used to assess positive youth development among Chinese adolescents. It has 15 subscales corresponding to 15 positive youth development attributes: bonding, resilience, social competence, recognition for positive behavior, emotional competence, cognitive competence, behavioral competence, moral competence, self-determination, self-effi cacy, clear and positive identity, beliefs in the future, prosocial involvement, prosocial norms, and spirituality.…”
Section: Instrumentsmentioning
confidence: 99%
“…General positive youth development qualities were scored by averaging the scores on each subscale. This measure has good reliability and validity (Shek et al 2007 ;…”
Section: Instrumentsmentioning
confidence: 99%